Phosphate availability conditions caspofungin tolerance, capsule attachment and titan cell formation in Cryptococcus neoformans - Qu, Xianya; Bhalla, Kabir; Horianopoulos, Linda C.; Hu, Guanggan; Alcázar Magaña, Armando; Foster, Leonard J.; Roque da Silva, Leandro Buffoni; Kretschmer, Matthias; Kronstad, James W. (Frontiers in Fungal Biology, 2024)
There is an urgent need for new antifungal drugs to treat invasive fungal diseases.Unfortunately, the echinocandin drugs that are fungicidal against other important fungal pathogens are ineffective against Cryptococcus neoformans, the causative agent of life-threatening meningoencephalitis in immunocompromised people. Contributing mechanisms for echinocandin tolerance are emerging with connections to calcineurin signaling, the cell wall, and membrane composition. In this context, we discovered that a defect in phosphate uptake impairs the tolerance of C. neoformans to the echinocandin caspofungin. Our previous analysis of mutants lacking three high affinity phosphate transporters revealed reduced elaboration of the polysaccharide capsule and attenuated virulence in mice. We investigated the underlying mechanisms and found that loss of the transporters and altered phosphate availability influences the cell wall and membrane composition. These changes contribute to the shedding of capsule polysaccharide thus explaining the reduced size of capsules on mutants lacking the phosphate transporters. We also found an influence of the calcineurin pathway including calcium sensitivity and an involvement of the endoplasmic reticulum in the response to phosphate limitation. Furthermore, we identified membrane and lipid composition changes consistent with the role of phosphate in phospholipid biosynthesis and with previous studies implicating membrane integrity in caspofungin tolerance.Finally, we discovered a contribution of phosphate to titan cell formation, a cell type that displays modified cell wall and capsule composition. Overall, our analysis reinforces the importance of phosphate as a regulator of cell wall and membrane composition with implications for capsule attachment and antifungal drug susceptibility.